Pola Asuh Orang Tua di Era Digital dan Globalisasi Terhadap Pembentukan Karakter Anak Usia Dini - Dinda Salsabila; Faisa Rahma Safira Siregar; Najwa Dwi Aprillia; Masganti Sit (CV Edujavare Publishing, 2025)
The digital era and globalization have brought significant changes to early childhood parenting patterns. Parents now face new challenges in the form of strong technological exposure to children's behavior and character. This study aims to analyze parenting patterns in the digital era and globalization and their implications for early childhood character development. This study used a descriptive qualitative approach with interviews and documentation methods involving four parents at TK An-Nida Medan as key informants. The data were strengthened by a literature review of books and scientific journals published between 2020 and 2025. The results show that parenting patterns in the digital era have shifted from traditional patterns to digital-adaptive patterns that emphasize technological literacy, open communication, and moral supervision. Parents who implement digital-authoritative patterns show positive character development outcomes, such as discipline, responsibility, empathy, and religiosity in children. Meanwhile, digital-permissive patterns tend to weaken children's self-control and reduce social interaction. This study emphasizes the importance of collaboration between parents, schools, and the environment in shaping early childhood character amidst the currents of globalization and digitalization